Backsplicing of the HIV-1 transcript generates multiple circRNAs to promote viral replication - Christopher Mauer; Sean Paz; Massimo Caputi (npj Viruses)
Abstract Circular RNAs (circRNAs) are a family of non-coding RNAs that originate from a non-canonical splicing event (backsplicing) that forms covalently closed continuous loops. An analysis of the human immunodeficiency type 1 virus (HIV-1) complex splicing pattern indicated that the virus had the potential to generate at least 15 distinct circRNAs. The predicted HIV circRNAs were amplified utilizing divergent PCR primers and confirmed by RNase R digestion and sequencing. A predictive circRNA-miRNA interaction modeling approach and a series of validation assays determined that two cellular miRNAs, miR-6727-3p and miR-4722-3p, functionally interact with a sequence present in 8 of the HIV circRNAs. Expression of miR-6727-3p and miR-4722-3p restricted HIV-1 replication while a circRNA containing the sequence recognized by miR-6727-3p and miR-4722-3p increased the production of infective virions. Additionally, miR-6727-3p and miR-4722-3p expression was upregulated following HIV-1 infection of primary CD4+ T cells. Overall, the data presented shows that HIV-1 generates circRNAs which promote viral replication by sequestering and inhibiting the functions of miR-6727-3p and miR-4722-3p.